Self-Transcendence in Mountaineering and BASE Jumping - Monasterio, Erik; Cloninger, C. Robert (Frontiers in Psychology, 2019)
The “extreme sports” of mountaineering and BASE Jumping are growing in popularity and are associated with significant risk of injury and death. In recent years there have also been increasing numbers of reports of reckless disregard and selfishness in the pursuit of mountaineering goals, including severe environmental degradation. Extant research has focused predominantly on personality variables that contribute to engagement, participation and stress responsivity in these extreme sports. The Temperament and Character Inventory provides a comprehensive account of personality traits, measuring seven dimensions of personality that are moderately heritable and associated with distinct brain networks and psychological characteristics. One of these traits is Self-Transcendence, which is associated with spiritual ideas and experiences, such as searching for something elevated and greater than one's individual self. High Self-Transcendence can motivate people to act altruistically even if that requires personal sacrifices and hardship. This article draws on the extant research literature, which has consistently found that despite substantial heterogeneity in their individual personality profiles, mountaineers and BASE jumpers are adventurous in temperament and highly self-controlled and organized in character. Between 75% and 85% of the character configurations observed in these populations are associated with low Self-Transcendence. The purpose of this paper is to consider the role of Self-Transcendence and its effect on individual personality profiles of extreme athletes, in particular in moderating potentially self- destructive, and regressive ethical and moral behaviors in mountaineering and BASE jumping.